The Pharmacists’ Role in Reducing Drug-Related Problems in Cardiology Center in Baghdad -Iraq: A Pilot Study - Farah Abdul-Kareem; Mohammed Y. Jamal (Iraqi Journal of Pharmaceutical Sciences, 2025)
Pharmacotherapy is essential to lower the morbidity and mortality associated with cardiovascular diseases. Patients with cardiovascular (CV) disease are often given polypharmacy which increases both the incidence of errors in prescriptions and the associated complications of medications. The objective of this study was to disclose the impact of clinical pharmacist contributions on drug-related problems (DRPs) in patients with CV disease, educated the patients about the importance of adherence to their medication, and evaluated the Pharmaceutical Care Network Europe (PCNE) version 9.1 can provide a suitable tool for the DRP process for Iraqi clinical pharmacists during routine work in CV setting. A prospective, interventional, clinical study was conducted in Iraq -Baghdad at Ibn- AL-Bitar Center for cardiac surgery, involving 52 patients. The researcher routinely screens the medical files of patients and conducts, and records any DRP, the classification of DRP using PCNE V 9.1. The researcher interviews patients and cardiologists and intervenes with the treatment to increase awareness about DRP. The degree of approval from a physician for interventions was also recorded. The researcher checked adherence based on the pill count method. Therapy and dosage schedules are evaluated based on the most recent therapeutic strategies guidelines (European Society of Cardiology 2021). Any potential adverse drug reactions (ADRs) or drug-drug interactions are evaluated. Interventions were commenced by the researcher, including patient counseling, medication initiation, medication adjustment, clarification of drug dosage and frequency, identification of contra-indication and incorrect indications, patient education, and patient counseling for lifestyle modifications. The most frequent problems found were adverse effects of drugs 48.1%, the potential problem 46.2% and the manifested problem 32.7%. 50.0% of DRPs are related to drugs unavailable. The most prevailing pharmacist intervention was intervention discussed with the prescriber (48.1%), patient counseling, spoken to family member (34.6%), then at drug level dosage changed (17.3%), drug changed, and drug stopped (13,5%), then drug started (11.5%). Patients with CV disease have a significant prevalence of drug-related problems. Pharmacists play an important role in recognizing and reducing the incidence of DRPs and the interventions they provided were well-accepted.